Hubungan Kadar Hemoglobin dengan Infeksi Kecacingan Soil Transmitted Helminth (STH) Pada Anak Sekolah Dasar di SDN Sungai Batang 1 Kabupaten Banjar - Unnufus, Ihya; Rifqoh, Rifqoh; Muhlisin, Ahmad; Kustiningsih, Yayuk (Jaringan Laboratorium Medis, 2024)
Worm infections are still a problem in Indonesia, one of which is South Kalimantan Province. This infection often occurs in elementary school children whose activities are often related to soil. Soil Transmitted Helminth (STH) infection in children causes intestinal inflammation, malnutrition and blood loss causing hemoglobin levels to decrease resulting in anemia. This study aims to determine the relationship between hemoglobin levels and STH worm infections in elementary school children at SDN Sungai Batang 1, Banjar Regency. This type of research is an analytical survey with a cross-sectional design. The population of this study was children in grades 1-6 at SDN Sungai Batang 1, totaling 47 people. Sample determination was carried out using total sampling technique. Hemoglobin levels were obtained from the results of examining capillary blood specimens using the Point of Care Testing (POCT) method using the Easy-Touch-GCHb tool, units gr/dL. STH worm infection is obtained from the results of microscopic examination of worm eggs in fresh fecal specimens using the Kato-Katz method with Eggs Per Gram (EPG) units. The results showed that 11 of 47 (23.41%) children were positive for STH infection, namely 5 (10.64%) Ascaris lumbricoides, 5 (10.64%) Trichuris trichiura and 1 (2.13%) were infected with both, with a total of 24 eggs. -48 EPGs. Hemoglobin levels ranged from 11.1 to 14.8 g/dL (mean 13.1 g/dL). Hemogobin levels were less than normal (12.0 gr/dL) in 11 of 47 (23.41%) children and normal hemoglobin levels in 36 (76.59%) children. The results of the Spearman rank coefficient test showed p 0.001, it can be concluded that there is a significant relationship between hemoglobin levels and STH worm infections in elementary school children at SDN Sungai Batang 1, Banjar Regency. It is recommended for future researchers to analyze the relationship between STH infection and erythrocyte index.